Magnetic field modelling and analysis of uncertainty in archaeological geophysics. Issue 2 (19th November 2018) - Schettino, Antonio; Ghezzi, Annalisa; Pierantoni, Pietro Paolo
Abstract: One of the major problems in the forward modelling of magnetic anomalies is the assessment of a minimum level of acceptable accuracy in the fit between observed and theoretical anomalies. We present a new approach to the analysis and interpretation of archaeological magnetic anomalies, based on classical algorithms of forward modelling and a new technique of error assessment. This approach allows us to determine geometry, physical properties, and location of buried archaeological features, as well as the occurrence of fires or other historical events that may have affected the observed magnetic signal. Our method starts from the acquisition of total field data, usually in a regular grid arrangement, and proceeds through their reduction to archaeological magnetic anomalies. This reduction is performed subtracting from the observed total field data a polynomial representation of the regional field, on the basis of a rigorous criterion that tries to separate archaeological anomalies from geological (crustal) contributions. At the next step, a map of the maximum allowed misfit is built, which depends from the estimated uncertainty at each point of the magnetic anomaly field. This map specifies the maximum allowed deviation of theoretical anomalies from the observed values. The last step is the analysis of these anomalies through a new forward modelling tool, with the objective to reconstruct the three‐dimensional arrangement of buried features and possibly obtain some information about the history.